Initial development amendoinzeiro under different matocompetition densities with Urochloa - Lisboa, Lucas Aparecido Manzani [UNESP]; Viana, Ronaldo da Silva [UNESP]; Ribeiro, Filipe Virgílio [UNESP]; de Figueiredo, Paulo Alexandre Monteiro [UNESP]; Ramos, Sérgio Bispo [UNESP] (Revista de Agricultura Neotropical, 2019)
Grasses and legumes compete in productive systems, and this competition depends on their specific survival skills. The objective of this work was to evaluate the initial development of peanut under different densities of competition with Urochloa. An experiment was carried out with a completely randomized design, in a 4 x 5 factorial scheme. The first factor was composed of four types of grasses, that is, Urochloa brizantha cv. Paiaguás; Marandu; Piatã and Urochloa ruziziensis, the second factor was composed of five densities of weed competition and five replications, totalizing 100 plots or vessels. After 30 days of sowing, the following parameters were determined: ISPADA - peanut spad index; CEA - stomatal peanut conductance; DCA - peanut stem diameter; APA and APG - plant height of peanut and grass; MSPAA and MSPAG - dry mass of aerial part of peanut and grass and MSRA and MSRG - dry mass of peanut root and grass. The peanut tree responds negatively when subjected to high weed competition densities with grasses of the genus Urochloa. Urochloa ruziziensis showed a greater weed competition in the initial development of the peanut tree.
Desenvolvimento inicial do amendoinzeiro sob diferentes densidades de matocompetição com Urochloa
Keywords: Arachis hypogaea; Marandu; Paiaguás; Piatã; stress